(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
This study aims at describe the role of the Central Bank in maintaining liquidity through mechanisms that can be applied in commercial banks operating in Iraq. The study attempted to determine indicators for measuring and monitoring the liquidity and it is reflection on the monetary and financial market to ensure the ability of the banks to meet their financial obligations which call these banks to adopt a renewal able strategy through taking in to consideration the studies of Economic feasibility to Evaluate the performance specifications according to the serves measures in the international banking , Then We chose The private Iraqi Bank and Bank the economy Bank for investment and financing as case as study .